1996
DOI: 10.1111/j.1751-1097.1996.tb02992.x
|View full text |Cite
|
Sign up to set email alerts
|

Probing Bile Salt Aggregates by Fluorescence Quenching

Abstract: Abstract— The combination of steady‐state and time‐resolved quenching experiments was employed to study the aggregation behavior of sodium cholate at concentrations below 50 mAf. Naphthalene, anthracene and pyrene were used as fluorescent probe molecules, and protection by the aggregates from aqueous quenchers, as well as the onset of aggregation at low sodium cholate concentrations, was dependent on the shape of the probes. Protection from aqueous quenchers was inferred by comparing the efficiency for dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(101 citation statements)
references
References 21 publications
5
96
0
Order By: Relevance
“…13 The dynamic studies were performed at NaC and NaTC concentrations above 20 mM, where primary aggregates were fully formed. In the case of NaC, this was confirmed by the observation that the protection of excited singlet naphthalene by the bile salt aggregates did not increase for NaC concentrations above 20 mM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…13 The dynamic studies were performed at NaC and NaTC concentrations above 20 mM, where primary aggregates were fully formed. In the case of NaC, this was confirmed by the observation that the protection of excited singlet naphthalene by the bile salt aggregates did not increase for NaC concentrations above 20 mM.…”
Section: Discussionmentioning
confidence: 99%
“…Previous fluorescence studies indicated that when naphthalene was incorporated into the hydrophobic sites of primary aggregates, it was well-protected from quenchers which primarily reside in the aqueous phase, as attested by the decrease of the rate constant for the dynamic quenching of this naphthalene population. 13 In the case of the triplet xanthone the hydrophobic and hydrophilic solubilization sites (Scheme 1) were possible candidates for the incorporation of this probe, and our studies indicate that this probe is located in a different environment than naphthalene.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…[10] Under different conditions, such as different solvent polarity,p H, and temperature, the behavior and conformation of cholate derivatives would be different. [11] Early studies on structural aspects have shown that cholate aggregates progressively to form micelles, [12] leading to thef ormation of larger structures as the concentrationo fc holate monomers increases. The primary/ secondary aggregationm odel proposes the association of the hydrophobic faces, in which as mall number of monomerslead to primarya ggregation at al ow concentration.A th igh monomer concentrations, the primary aggregation agglomerates into larger structures called secondary aggregates.…”
Section: Introductionmentioning
confidence: 99%